Seizure in nontraumatic subarachnoid hemorrhage - Eugenia I. Tsoma (Ukrainian Neurosurgical Journal, 2018)
Seizures are quite common in aneurysmal subarachnoid hemorrhage (SAH). The prevalence is from 6 to 24% in all non-traumatic subarachnoid hemorrhages. They can be early – develop within first two weeks, or late seizures, that can become symptomatic post-stroke epilepsy. Quite often (13-24%) seizure can be the first clinical symptom of SAH, concomitant or isolated from thunderclap headache. Other factors, such as low Hunt-Hess, WFNS, GCS in onset, intracerebral hematoma, obstructive hydrocephalus, symptomatic vasospasm are associated with worse prognosis. But the influence of seizure for patient’s outcome is open to debate and is the least studied issue. Accordingly to this, there are no clear recommendations or guidelines for anticonvulsive therapy for primary and secondary prevention and improvement of the prognosis for a patient with SAH. The aim of this article is to review the literature and research data of recent years in order to find out the place of seizures in subarachnoid hemorrhage.